1996
DOI: 10.1113/jphysiol.1996.sp021296
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous and exogenous dopamine depress EPSCs in rat nucleus accumbens in vitro via D1 receptors activation.

Abstract: Birw-inltghazt B15 2TT, UK 1. Whole-cell patch clainp recordings were made fiom nucleus accumbens neurones in slices of rat ventral forebrain. In the presence of piciotoxin (50 /tM), the amplitude of 6-cyano-7-nitroquinoxaline-2,3-dione-sensitive glutamate EP8Cs, recorded at holding potentials between -80 and -90 mV, was reversibly reduced by 56 + 11 % (ra = 6) by dopamine (30 AM). The selective dopamine D1 receptor agonists SKF 38393 (10 AM) and SKF 81297A (10 /tM), but not the selective D2 receptor agonist q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
97
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(115 citation statements)
references
References 19 publications
17
97
1
Order By: Relevance
“…Furthermore, our pharmacological studies revealed that the action of DA was mediated via the activation of presynaptically located D 1 -like receptors. Similar reduction of excitatory transmission mediated by presynaptic D 1 -like receptors has been reported in nucleus accumbens (Pennartz et al, 1992;Harvey and Lacey, 1996;Nicola et al, 1996). In contrast, information regarding the effect of DA on inhibitory synaptic transmission in basal forebrain is sparse, although it has been known that iontophoretic application of DA attenuated the inhibitory action of iontophoretically administered GABA on the firing rates of neurons within the globus pallidus (Bergstrom and Walters, 1984).…”
Section: Abstract: Dopamine; D 1 Receptor; Inhibitory Postsynaptic Cmentioning
confidence: 52%
“…Furthermore, our pharmacological studies revealed that the action of DA was mediated via the activation of presynaptically located D 1 -like receptors. Similar reduction of excitatory transmission mediated by presynaptic D 1 -like receptors has been reported in nucleus accumbens (Pennartz et al, 1992;Harvey and Lacey, 1996;Nicola et al, 1996). In contrast, information regarding the effect of DA on inhibitory synaptic transmission in basal forebrain is sparse, although it has been known that iontophoretic application of DA attenuated the inhibitory action of iontophoretically administered GABA on the firing rates of neurons within the globus pallidus (Bergstrom and Walters, 1984).…”
Section: Abstract: Dopamine; D 1 Receptor; Inhibitory Postsynaptic Cmentioning
confidence: 52%
“…Stimulation of the VTA in vivo or activation of dopamine receptors in vitro attenuates the responses of accumbens neurons to stimulation of the amygdala or hippocampus (Yang and Mogenson, 1984;Yim and Mogenson, 1988;Charara and Grace, 2003). The amplitude of PFC-evoked EPSPs is also decreased after application of dopamine agonists in vitro (Pennartz et al, 1992;O'Donnell and Grace, 1994;Harvey and Lacey, 1996). Thus, as proposed by Mogenson et al (1988), the primary function of dopamine in the nucleus accumbens appears to be to modulate the effects of excitatory limbic and cortical inputs rather than to drive neuronal activity directly (O'Donnell, 1999;Nicola et al, 2000).…”
Section: Vta Modulation Of Cortical Inputs To the Nucleus Accumbensmentioning
confidence: 90%
“…Although previous in vitro experiments have reported a selective modulation of PFC inputs to the accumbens by a D 1 -like mechanism (Pennartz et al, 1992;Harvey and Lacey, 1996;Nicola et al, 1996), we found no evidence for a role of D 1 receptors in the suppression of prefrontal inputs in vivo, using a selective D 1 antagonist (SCH 23390) at a dose that effectively attenuates responses to VTA stimulation in PFC pyramidal neurons (Lewis and O'Donnell, 2000) or, in conjunction with a D 2 antagonist, in accumbens neurons (Goto and O'Donnell, 2001). Differences between recording conditions, specific antagonists, and/or placement of recording and stimulating electrodes could account for these disparities.…”
Section: Mechanisms Of Dopaminergic Modulation Of Pfc Inputsmentioning
confidence: 96%
See 2 more Smart Citations